Porosity effects of AlSi10mg parts produced by selective laser melting - Hasmuni, Noreriyanti; Ibrahim, Mustaffa; Raus, Azli Amin; Wahab, Mohd Saidin; Kamarudin, Khairu (Faculty of Mechanical Engineering, Universiti Teknologi MARA (UiTM, 2018)
Selective Laser Melting (SLM) is one of the powder-based manufacturing processes that has a wider established uses in the production of metallic alloy parts. It is capable of producing a high-density part through the melting of powder to form the desired shape. Fabrication of the AlSI10Mg part relies on several process parameters such as the laser power, laser scan speed, hatch distance, layer thickness and scanning strategy. They are specially designed and monitored to achieve optimum level. In this paper, porosity percentage were obtained from manipulating the hatch distance of fabricated SLM parts. The results appeared that smallest percentage obtained when the hatch distance was 0.13mm which is 0.46%. However, the highest porosity obtained when the lower hatch distance applied.